2009
DOI: 10.1111/j.1365-2486.2008.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon losses due to soil warming: Do autotrophic and heterotrophic soil respiration respond equally?

Abstract: Global warming has the potential to increase soil respiration (R S ), one of the major fluxes in the global carbon (C) cycle. R S consists of an autotrophic (R A ) and a heterotrophic (R H ) component. We combined a soil warming experiment with a trenching experiment to assess how R S , R A , and R H are affected. The experiment was conducted in a mature forest dominated by Norway spruce. The site is located in the Austrian Alps on dolomitic bedrock. We warmed the soil of undisturbed and trenched plots by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
147
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 64 publications
17
147
3
1
Order By: Relevance
“…The basal CO 2 efflux at 10 • C (F 10 ) was 30-40 % lower when compared to the control stands (Table 3). This percentage corresponds roughly to the autotrophic contribution to F soil in intact forest ecosystems similar to ours (Hanson et al, 2000;Schindlbacher et al, 2009). However, as measured F soil rates between the young windthrow areas and control stands were not statistically different (Table 2), it appears that the decrease in autotrophic soil respiration was in fact offset by accelerated heterotrophic soil respiration, i.e.…”
Section: Discussionmentioning
confidence: 57%
“…The basal CO 2 efflux at 10 • C (F 10 ) was 30-40 % lower when compared to the control stands (Table 3). This percentage corresponds roughly to the autotrophic contribution to F soil in intact forest ecosystems similar to ours (Hanson et al, 2000;Schindlbacher et al, 2009). However, as measured F soil rates between the young windthrow areas and control stands were not statistically different (Table 2), it appears that the decrease in autotrophic soil respiration was in fact offset by accelerated heterotrophic soil respiration, i.e.…”
Section: Discussionmentioning
confidence: 57%
“…As a result, there is a very thick surface organic layer and no distinct soil stratification. The carbon content of the top 30-cm-thick soil layer (17.691.6 kg C m (2 ) is similar to the mean value in the surface layer of Japanese peatland soils (17.2 kg C m Morisada et al, 2004) and much higher than the mean global estimate of 11.3 kg C m (2 for the 100-cm-thick surface soil layer (Sombroek et al, 1993). The soil heterotrophic respiration rate of 3.2 and 5.8 kg C m (2 at unwarmed and warmed trenched treatments, respectively, during the four snow-free seasons from 2008 to 2011 (838 d) accounts for 18 and 33% of the measured soil carbon content in the surface 30-cm-thick layer.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, Niinisto¨et al (2004) reported 27Á43% rise in soil CO 2 efflux during a 4-yr warming experiment (3Á68C increase in air temperature) in a 20-yr-old Scots pine forest, and Bronson et al (2008) found that the soil CO 2 efflux was increased by 24 and 11% in the first and second year, respectively, by soil warming (58C increase in soil temperature) in a black spruce forest. Schindlbacher et al (2009) reported a 39 and 45% increase in the soil heterotrophic respiration in the first and second year, respectively, by soil warming (48C increase in soil temperature) in a mature forest dominated by Norway spruce.…”
Section: Discussionmentioning
confidence: 99%
“…light intensity and plant phenology (Epron et al 2001;Janssens & Pilegaard 2003). Schindlbacher et al (2009) therefore concluded that only responses measured under experimental warming reflect the true soil respiration sensitivity to warming. Recent studies applying experimental warming agreed on bulk-soil respiration to be more temperature-sensitive than root and rhizosphere respiration Vogel et al 2014;Wang et al 2014).…”
Section: Discussionmentioning
confidence: 99%